2014
DOI: 10.1038/leu.2014.55
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of genetic alterations and their prognostic impacts in adult acute myeloid leukemia patients

Abstract: To clarify the cooperative roles of recurrently identified mutations and to establish a more precise risk classification system in acute myeloid leukemia (AML), we comprehensively analyzed mutations in 51 genes, as well as cytogenetics and 11 chimeric transcripts, in 197 adult patients with de novo AML who were registered in the Japan Adult Leukemia Study Group AML201 study. We identified a total of 505 mutations in 44 genes, while only five genes, FLT3, NPM1, CEBPA, DNMT3A and KIT, were mutated in more than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
174
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(187 citation statements)
references
References 43 publications
6
174
2
2
Order By: Relevance
“…Co-occurrence of FLT3-ITD and MLL-PTD has been reported previously in AML, though the significance of this finding on outcome or response is currently unknown. 15 The potential use of demethylating agents and histone deacetylase inhibitors, as has been proposed for cases of MLL-PTD AML, 3,9 is one area of further exploration. Of note, de novo MLL-PTD AML patients, which exclude patients with underlying MDS, showed the best outcomes of patients in this study, possibly due to early transplantation, and may have better prognosis than has been previously reported.…”
Section: Mll-ptdmentioning
confidence: 99%
“…Co-occurrence of FLT3-ITD and MLL-PTD has been reported previously in AML, though the significance of this finding on outcome or response is currently unknown. 15 The potential use of demethylating agents and histone deacetylase inhibitors, as has been proposed for cases of MLL-PTD AML, 3,9 is one area of further exploration. Of note, de novo MLL-PTD AML patients, which exclude patients with underlying MDS, showed the best outcomes of patients in this study, possibly due to early transplantation, and may have better prognosis than has been previously reported.…”
Section: Mll-ptdmentioning
confidence: 99%
“…In recent years, the use of next-generation sequencers has facilitated energetic exploration of gene mutations, leading to the discovery of other AML-related gene mutations, [14][15][16][17] and mutations in the genes that regulate DNA methylation, such as DNA methyltransferase 3 alpha (DNMT3A), Tet methylcytosine dioxygenase 2 (TET2), isocitrate dehydrogenase1 (IDH1), and isocitrate dehydrogenase 2 (IDH2). [18][19][20][21][22][23] It has been suggested that these gene mutations may also have prognostic relevance in some cases of AML, but this view has yet to become established.…”
Section: Clinical Characteristics and Prognosis Of Acute Myeloid Leukmentioning
confidence: 99%
“…Acute myeloid leukemias (AML) comprise a heterogeneous group of diseases (11)(12). Evidence accumulated that AMLs are maintained by a population of leukemic stem cells (LSC, leukemia initiating cells, leukemia stem-like cells) that are resistant to conventional chemotherapy, and likely are responsible for relapses (7)(8)13).…”
Section: Introductionmentioning
confidence: 99%